Chip is an essential cofactor for Apterous in the regulation of axon guidance in Drosophila. - van Meyel, D.J.; O'Keefe, D.D.; Thor, S.; Jurata, L.W.; Gill, G.N.; Thomas, J.B. (Development, 2000)
LIM-homeodomain transcription factors are expressed in subsets of neurons and are required for correct axon guidance and neurotransmitter identity. The LIM-homeodomain family member Apterous requires the LIM-binding protein Chip to execute patterned outgrowth of the Drosophila wing. To determine whether Chip is a general cofactor for diverse LIM-homeodomain functions in vivo, we studied its role in the embryonic nervous system. Loss-of-function Chip mutations cause defects in neurotransmitter production that mimic apterous and islet mutants. Chip is also required cell-autonomously by Apterous-expressing neurons for proper axon guidance, and requires both a homodimerization domain and a LIM interaction domain to function appropriately. Using a Chip/Apterous chimeric molecule lacking domains normally required for their interaction, we reconstituted the complex and rescued the axon guidance defects of apterous mutants, of Chip mutants and of embryos doubly mutant for both apterous and Chip. Our results indicate that Chip participates in a range of developmental programs controlled by LIM-homeodomain proteins and that a tetrameric complex comprising two Apterous molecules bridged by a Chip homodimer is the functional unit through which Apterous acts during neuronal differentiation.